Labor productivity growth and industrialization in Africa - McMillan, Margaret S.; Zeufack, Albert (American Economic Association, 2022)
Manufacturing has made an important contribution to raising living standards in many parts of the world. Concerns about premature deindustrialization have made some observers skeptical about the potential for manufacturing to play this role in Africa. But employment in African manufacturing has grown rapidly over the past 20 years. These employment gains have been accompanied by: (i) large increases in the number of small manufacturing firms; (ii) limited employment gains in large firms; and (iii) robust labor productivity growth in Africa’s large firms. Limited employment growth in Africa’s large manufacturing firms is partly a result of the capital intensity of the manufacturing subsectors in which African countries are most engaged—the processing of resources—and partly a result of rising capital intensity in manufacturing. The potential for manufacturing to raise living standards in Africa depends on indirect job creation by large firms through backward and forward linkages and increasing labor productivity in small firms.